O canto coletivo de Cuiabá no universo virtual - Ferreira, Marta Martines (2013)
This essay is the result of a mastering research developed along with the Graduation Program in Contemporary Culture Studies - Mastering degree– from the Federal University of Mato Grosso. The aim of this research was to investigate the process of adaptation from collective singing groups, in the city Cuiabá, state of Mato Grosso in the cyberculture scenario. This research debates cultural changes that come from virtual accessibility over the internet, the advancement of technologies and its influence in the contemporary musical panorama, considering that collective singing remains an unexplored theme in cyberculture, despite its appearance in the musical environment. Focused on analyzing implications of the uses of digital technologies in feasible modification about practices and musical diffusion, a qualitative search was proposed supported by bibliographic and field search. Authors who discuss the cyberculture universe, the uses of social network to disclose themselves and their works as well as collective singing were consulted. The field search happened along with institutions that promote cultural events and also with the collective singing groups regents; it aims to know the scenario of music in collective singing mode in Cuiabá, the places offered to groups and ways of disclosure. Furthermore, there was a research over the internet in order to seek websites from groups that frequently have presentations in these events and how their regents or representative institution understand the couplings of cultural practices in cyberspace, besides the implications in the scenario of musical culture in the city of Cuiabá. The results show that few leaders have demonstrated understanding of the potential of the Internet in their work, not using it properly for the benefit of the chanting of the region. Cyberspace does not seem to present to the regents as a space in its scope can strengthen the practice through an innovative approach to his work as a diffuser and mediator of culture in the field of music